2022
DOI: 10.51800/ecd.1054815
|View full text |Cite
|
Sign up to set email alerts
|

Analitik Hiyerarşi Süreci (AHS) İle Delibekirli (Kırıkhan/Hatay) Havzası’nın Kütle Hareketleri Duyarlılık Analizi

Abstract: Birbirinden farklı köken ve ölçekteki faktörlerin oluşturduğu süreçlerle gerçekleşen heyelanların yol açtığı can kayıplarının sayısı ile ekonomik kayıpların miktarı oldukça fazladır. Herhangi bir sahada yaşanabilecek heyelan potansiyelinin önceden tespit edilmesi ve bu tespitlerin arazi kullanım planlamalarında göz önünde bulundurulması heyelanlarla olması muhtemel kayıpların önüne geçilmesini sağlayacaktır. Bu çalışmada, Amanos Dağları’nın orta kesiminde yer alan yaklaşık 52 km2 alan kaplayan Delibekirli Havz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As the slope values increase and accordingly the slope stability deteriorates, the balance of the material on the slope deteriorates, and slips along the slope occur. The slope values reclassi ed into ve classes as very low (< 5), low (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), high (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), very high (45-60), and extreme (> 60). The vegetation type, microclimate, rainfall, and runoff process can be affected by elevation.…”
Section: #Fig 2 Approximately Here#mentioning
confidence: 99%
See 2 more Smart Citations
“…As the slope values increase and accordingly the slope stability deteriorates, the balance of the material on the slope deteriorates, and slips along the slope occur. The slope values reclassi ed into ve classes as very low (< 5), low (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), high (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), very high (45-60), and extreme (> 60). The vegetation type, microclimate, rainfall, and runoff process can be affected by elevation.…”
Section: #Fig 2 Approximately Here#mentioning
confidence: 99%
“…Özçelik and Buğday (2022) generated LSM by using GIS-based AHP approach and determined that distance to faults was the highest weight value, and followed by slope. Another study from Delibekirli watershed in Hatay showed that precipitation (1.125), lithology (0.204), slope (0.162), and curvature (0.15) were the most effective parameters for landslide according to AHP weights (Bozdoğan and Canpolat, 2022). Buğday and Akay (2022) revealed LSM by using LR and RF approach and determined that aspect, lithology, elevation, slope, distance to stream, SPI, TWI, distance to roads, and distance to faults were the most signi cant factors.…”
Section: Landslide Susceptibility Mapmentioning
confidence: 99%
See 1 more Smart Citation